Characterization and functional analysis of chicken APOBEC4. (May 2020) - Shi, Mengyu; Tan, Lei; Zhang, Yaodan; Meng, Chunchun; Wang, Wei; Sun, Yingjie; Song, Cuiping; Liu, Weiwei; Liao, Ying; Yu, Shengqing; Ren, Tao; Ding, Zhuang; et al.
Abstract: The APOBEC proteins play significant roles in the innate and adaptive immune system, probably due to their deaminase activities. Because APOBEC1 (A1) and APOBEC3 (A3) are absent in the chicken genome, we were interested in determining whether chicken APOBEC4 (A4) possessed more complex functions than its mammalian homologs. In this study, chicken A4 (chA4) mRNA was identified and cloned for the first time. Based on bioinformatics analyses, the conserved zinc-coordinating motif (HXE … PC(X)2–6 C) was identified on the surface of chA4 and contained highly conserved His97, Glu99, Pro130, Cys131 and Cys138 active sites. The highest expression levels of constitutive chA4 were detected in primary lymphocytes and bursa of Fabricius. Newcastle Disease (ND) is one of the most serious infectious diseases in birds, causing major economic losses to the poultry industry. In vitro, Newcastle Disease Virus (NDV) early infection induced significant increases in chA4 expression in the chicken B cell line, DT40, the macrophage cell line, HD11 and the CD4 + T cell line, MSB-1, but not the fibroblast cell line, DF-1. In vivo, the expression levels of chA4 were up-regulated in several tissues from NDV-infected chickens, especially the thymus, testicles, duodenum and kidney. The high level expression of exogenous chA4 displayed inhibitory effects on NDV and reduced viral RNA in infected cells. Taken together, these data demonstrate that chA4 is involved in the chicken immune system and may play important roles in host anti-viral responses. Highlights: First time isolation and identification of chicken APOBEC4. chA4 contains typical APOBEC motifs and probably has catalytic activity. The highest expression levels of constitutive chA4 were detected in primary lymphocytes and bursa of Fabricius. NDV infection induces significant increases in chA4 expression in immune cells and in the tissues of infected chickens. chA4 expression induces inhibitory effects on NDV.